Teen’s Anxiety Through Poetry: Love or Dream? - Idha Nurhamidah (Dinamika Bahasa dan Budaya, 2018)
Teens are identical with instability and anxiety for which they need to express as their individual self-actualization. So far there have been no such efforts to accommodate their needs through literary works. The current study explores the dictions employed in English poems written by the students (identified as teens) of English Letters Study Program to find about how far a poem can be as a means for teens to express their feelings. The subjects were assigned to write poems of their interests. The 32 poems were then analyzed and interpreted to find out how most students expressed their anxieties in terms of love to parents, love to boy/girlfriends, friendship, hope, admiration, disappointment, encouragement, divinity and educational goals. The findings indicate that they turn out to be able to write poems when they are emotionally touched. In particular, they employed a limited range of lexical items to express their love to their parents, boy/girlfriends, in addition to love to their college in pursuit of their educational goals. As the general practice of teaching literature ending up with the students’ analyzing literary works, it is high time that they were assigned to write poems to express their feelings. Keywords: anxieties, poem, love, emotionally touched